2015
DOI: 10.1007/s00280-015-2844-2
|View full text |Cite
|
Sign up to set email alerts
|

A clinical pharmacokinetic microdosing study of docetaxel with Japanese patients with cancer

Abstract: Docetaxel clearance showed marginal nonlinearity between microdose and therapeutic dose, presumably because of saturation of plasma protein binding; however, the magnitude was within twofold, allowing practically acceptable extrapolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Relevant publications reporting docetaxel PKs and toxicity or efficacy were retrieved. Twenty-two studies were included, 7 were excluded for lacking of AUC data (26-32), 3 were excluded for the lack of toxicity data (neutropenia) (33)(34)(35), 2 were excluded for liver disfunction enrollment (36,37), and 2 were excluded for the lack of correlation analysis (38,39). Totally, 8 studies were enrolled into this pooled analysis (5,(15)(16)(17)(18)(19)(20)(21).…”
Section: Preliminary Determination Of Target Auc From Pooled 8 Docetaxel Pk Studiesmentioning
confidence: 99%
“…Relevant publications reporting docetaxel PKs and toxicity or efficacy were retrieved. Twenty-two studies were included, 7 were excluded for lacking of AUC data (26-32), 3 were excluded for the lack of toxicity data (neutropenia) (33)(34)(35), 2 were excluded for liver disfunction enrollment (36,37), and 2 were excluded for the lack of correlation analysis (38,39). Totally, 8 studies were enrolled into this pooled analysis (5,(15)(16)(17)(18)(19)(20)(21).…”
Section: Preliminary Determination Of Target Auc From Pooled 8 Docetaxel Pk Studiesmentioning
confidence: 99%
“…First trials that used microdoses in patients (e.g. with cancer) have already been published [8]. Others investigated whether microdosing can be used to evaluate the effect of polymorphisms in SLCO1B1 (gene encoding for OATP1B1) and ABCG2 (gene encoding for BCRP) on OATP1B1 or BCRP substrate disposition [9].…”
Section: Expert Opinionmentioning
confidence: 99%
“…However, quantitative prediction of human PK can still be challenging, and phase 0/microdose studies can serve as a powerful complementary tool to existing approaches. Safely obtaining PK data is particularly valuable where a drug has a narrow therapeutic index (NTI), as is often the case with anticancer agents . The pivotal microdosing validation studies in the PK/bioavailability domain have been the CREAM (Consortium for Resourcing and Evaluating AMS Microdosing) and EUMAPP (European Microdosing accelerator mass spectrometry [AMS] Partnership Programme) trials in Europe, and the NEDO (New Energy and Industrial Technology Development Organization) trials in Japan .…”
Section: Past and Current Validation Efforts And Applicationsmentioning
confidence: 99%
“…Safely obtaining PK data is particularly valuable where a drug has a narrow therapeutic index (NTI), as is often the case with anticancer agents. 37,42,43 The pivotal microdosing validation studies in the PK/bioavailability domain have been the CREAM (Consortium for Resourcing and Evaluating AMS Microdosing) and EUMAPP (European Microdosing accelerator mass spectrometry [AMS] Partnership Programme) trials in Europe, and the NEDO (New Energy and Industrial Technology Development Organization) trials in Japan. 19,44,45 By now the results of more than 35 studies in both animals and humans have been reported comparing microdose vs. full dose.…”
Section: Pk and Bioavailabilitymentioning
confidence: 99%